Utilizing Mixed Methods Community-Based Participatory Research to Improve Environmental Health and Quality of Life Outcomes in Rural Rwanda - Leah Horton (Pan-African Journal of Health and Environmental Science)
Background: Health risks associated with burning biomass and stress on forests caused by firewood demand have necessitated improved cookstove programs. This study aimed to introduce and assess the functionality and impact of an intervention rocket cookstove in a rural Rwandan village.